Ultrasound-guided caudal anaesthesia combined with epidural anaesthesia for caesarean section: a randomized controlled clinical trial - Fangjun Wang; Qi Lü; Min Wang; Hongchun Xu; Dan Xie; Zheng Yang; Qin Ye (BMC Pregnancy and Childbirth, 2024)
Abstract Background Although epidural anaesthesia and spinal anaesthesia are currently the general choices for patients undergoing caesarean section, these two neuraxial anaesthesia methods still have drawbacks. Caudal anaesthesia has been considered to be more appropriate for gynaecological surgery. The purpose of this study was to compare epidural anaesthesia combined with caudal anaesthesia, spinal anaesthesia and single-space epidural anaesthesia for caesarean section with respect to postoperative comfort and intraoperative anaesthesia quality. Methods In this clinical trial, 150 patients undergoing elective caesarean section were recruited and randomized into three groups according to a ratio of 1:1:1to receive epidural anaesthesia only, spinal anaesthesia only or epidural anaesthesia combined with caudal anaesthesia. The primary outcome was postoperative comfort in the three groups. Secondary outcomes included intraoperative anaesthesia quality and the incidences of nausea, vomiting, postdural puncture headache, maternal bradycardia, or hypotension. Results More patients were satisfied with the intraoperative anaesthesia quality in the EAC group than in the EA group (P = 0.001). The obstetrician was more significantly satisfied with the intraoperative anaesthesia quality in the SA and EAC groups than in the EA group (P = 0.004 and 0.020, respectively). The parturients felt more comfortable after surgery in the EA and EAC groups (P = 0.007). The incidence of maternal hypotension during caesarean section was higher in the SA group than in the EA and EAC groups (P = 0.001 and 0.019, respectively). Conclusions Epidural anaesthesia combined with caudal anaesthesia may be a better choice for elective caesarean section. Compared with epidural anaesthesia and spinal anaesthesia, it has a higher quality of postoperative comfort and intraoperative anaesthesia.